2021
DOI: 10.1093/qjmed/hcab094.019
|View full text |Cite
|
Sign up to set email alerts
|

Construction of auditory bombardment therapy program: a pilot study

Abstract: Background Speech sound disorder is a communication disorder in which children have persistent difficulty saying words or sounds correctly. It refers to any difficulty or combination of difficulties with perception, motor production, or phonological representation of speech sounds and speech segments. Aim of the Work to construct an Arabic auditory bombardment therapy program and measure its effectiveness in treatment of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…During the last 30 years, number of studies showed limited effectiveness of auditory bombardment on functional speech sound disorders as there is no significant differences between using auditory bombardment as an adjunct to conventional therapy over the usage of conventional therapy alone [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…During the last 30 years, number of studies showed limited effectiveness of auditory bombardment on functional speech sound disorders as there is no significant differences between using auditory bombardment as an adjunct to conventional therapy over the usage of conventional therapy alone [45][46][47].…”
Section: Discussionmentioning
confidence: 99%